Visible Spectrophotometric Determination of Cefuroxime Sodium - Reddy, M.N.; Reddy, Y.P.N.; Reddy, P.J.C.; Murthy, T.K.; Srinivas Rao, Y. (Asian Journal of Chemistry, 2010)
Two simple spectrophotometric methods (A and B) have been developed for the determination of cefuroxime sodium in pure and in its pharmaceutical formulations. Method A is based on the formation of green coloured complex with ferric chloride and postassium ferricyanide exhibiting maximum aborption at 765 nm, whereas method B is based on the formation of blood red coloured complex with ferric chloride and 1,10-phenanthroline having absorption maximum at 510 nm. The results obtained are reproducible and are statistically validated.